DIFFERENCES IN SELF-CONTROL FROM GENDER, AGE AND BIRTH ORDER IN NAHDLATUL ULAMA 2 STUDENTS GRESIK - Nisya’, Choirun; Laily, Nadhirotul; Fitri Sholichah, Ima (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2021)
Students who can control themselves will not do wrong actions that they have experienced because they will understand that taking actions that violate the rules will get punishment consequences. Regarding gender, a person’s self-control is seen from gender, including roles, behavior, preferences, and other attributes that explain a particular culture. Based onAs children age, the communities that influence them increase, as well as the many social experiences they experience, children learn to respond to disappointments, dislikes, failures, and learn to control them, so that over time this self- control emerges from within itself. Birth order can affect a person’s self-control in various conditions including how the individual views the role that must be carried out. This study aims to determine differences in self-control in terms of gender, age and birth order in students. This study uses a quantitative method with a population of 547 students. In this case, the researcher uses a non-probability sampling technique with a proportionate stratified random sampling technique. The sample obtained is 241 students. The method collected using a questionnaire. This study uses a summative scale measurement, with a Likert scale type with 5 (five) alternative answers. Test the validity of the scale using content validity. The scale reliability test uses the Cronbach alpha technique. The data analysis technique used the t-test data analysis technique, the Independent Samples T-Test. The results showed that there was no significant difference between self-control with Gender, Age, and Birth Order